The Importance of Swelling Effects on Cathode Density and Electrochemical Performance of Lithium−Sulfur Battery Cathodes Produced via Dry Processing. Issue 2 (16th December 2021) - Schmidt, Florian; Ehrling, Sebastian; Schönherr, Kay; Dörfler, Susanne; Abendroth, Thomas; Althues, Holger; Kaskel, Stefan
Abstract : Lithium−sulfur batteries are promising candidates to satisfy the growing demand for high gravimetric, as well as high volumetric energy density batteries, due to their abundant and cost‐efficient raw‐materials. Consequently, this cell system has become an active subject of academic and industrial research. Therefore, new records for gravimetric, as well as volumetric energy densities have been reported in recent years. To further increase the volumetric energy density of the cells, the electrodes are often densified. Hence, the influence of the cathode density on the performance of lithium−sulfur batteries is still not fully understood. Herein, dry‐processed (DRYtraec) sulfur carbon cathodes with varying electrode densities are tested with ether‐based electrolytes under lean electrolyte (5 μL mg(s) −1 ) conditions. The electrochemical evaluation reveals that the density does not influence the performance of the cathodes at coin‐cell level as their density is altered upon electrolyte contact due to swelling. To monitor this, dynamic swelling experiments via confocal microscopy are conducted. Subsequently, the findings are transferred to investigate the influence of cathode swelling on the volumetric energy density. The influence of cathode swelling on the volumetric energy density of pouch cells is calculated based on the cathodes investigated at coin‐cell level. Abstract : Herein, solvent‐free sulfur/carbon cathodes, manufactured via DRYtraec process, are densified to increase their volumetric energy density. Their electrochemical performance is evaluated in ether‐based electrolytes on coin‐cell level. It is found that the initial densification of these cathodes has no significant influence on their performance, due to an expansion/swelling of the cathodes. The expansion/swelling is evaluated via confocal microscopy.